Interest rate expectations and uncertainty during ECB governing council days: evidence from intraday implied densities of 3-month Euribor - Olivier Vergote; Josep Maria Puigvert Gutiérrez (European Central Bank (ECB), 2011)
This paper analyses changes in short-term interest rate expectations and uncertainty during ECB Governing Council days. For this purpose, it first extends the estimation of risk-neutral probability density functions up to tick frequency. In particular, the non-parametric estimator of these densities, which is based on fitting implied volatility curves, is applied to estimate intraday expectations of threemonth EURIBOR three months ahead. The estimator proves to be robust to market microstructure noise and able to capture meaningful changes in expectations. Estimates of the noise impact on the statistical moments of the densities further enhance the interpretation. In addition, the paper assesses the impact of the ECB communication during Governing Council days. The results show that the whole density may react to the communication and that such repositioning of market participants' expectations will contain information beyond that of changes in the consensus view already observed in forward rates. The results also point out the relevance of the press conference in providing extra information and triggering an adjustment process for interest rate expectations.
Keywords: C14; E43; E52; E58; E61; 330; announcement effects; central bank communication; interest rate expectations; intraday analysis; option-implied densities; risk-neutral probability density functions; tick data